2011
DOI: 10.1136/hrt.2010.212621
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variations of infarct size in acute myocardial infarction

Abstract: BackgroundThe circadian clock influences a number of cardiovascular (patho)physiological processes including the incidence of acute myocardial infarction. A circadian variation in infarct size has recently been shown in rodents, but there is no clinical evidence of this finding. Objective To determine the impact of time-of-day onset of ST segment elevation myocardial infarction (STEMI) on infarct size. Methods A retrospective single-centre analysis of 811 patients with STEMI admitted between 2003 and 2009 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
158
5
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 36 publications
13
158
5
10
Order By: Relevance
“…In our series MV is a strong independent predictor for mortality, since MV patients are older, with a larger infarct size (as indicated by peak TnI) [18][19][20], hemodynamic impairment (as inferred by advanced Killip class) and a higher incidence of multi-organ dysfunction (as indicated by lower eGFR and a higher use of devices, often simultaneously implanted).…”
Section: Discussionmentioning
confidence: 99%
“…In our series MV is a strong independent predictor for mortality, since MV patients are older, with a larger infarct size (as indicated by peak TnI) [18][19][20], hemodynamic impairment (as inferred by advanced Killip class) and a higher incidence of multi-organ dysfunction (as indicated by lower eGFR and a higher use of devices, often simultaneously implanted).…”
Section: Discussionmentioning
confidence: 99%
“…Mukamal et al 19 reported that the highest peak creatine kinase levels occurred in patients with myocardial infarction whose symptoms commenced between midnight and 6 AM, and the highest incidence of heart failure was seen in patients whose symptoms began around midnight. In patients with acute ST-segment elevation myocardial infarction, Suarez-Barrientes 20 showed that maximum infarct size estimated by biomarker release, depression of left ventricular ejection fraction, and the incidence of clinical heart failure were all greater in patients whose infarcts occurred between 6 AM and noon. Arroyo Ucar et al 21 reported that infarct sizes were larger in patients with ST-segment elevation myocardial infarction whose symptoms began between midnight and noon than those occurring between noon and midnight.…”
mentioning
confidence: 99%
“…Two retrospective studies and one prospective study have independently demonstrated that a larger infarct size, estimated by biomarker release, in patients with ST-elevation MI undergoing primary percutaneous coronary intervention is associated with onset of symptoms in the sleep-wake transition. [53][54][55] However, a recent prospective multicenter, multiethnic cohort study did not find a clear circadian dependence of infarct size either in the entire data set or in each of the three participating countries separately. 56 Unlike symptoms of ischemia, infarct size is influenced not only by the circadian biology of the patient, but also by the circadian biology of their health care providers, who are shift workers themselves and under different levels of stress in a time-of-day-dependent manner.…”
Section: Myocardial Infarctionmentioning
confidence: 99%